Biosynthesis and heterologous production of furanocoumarins: perspectives and current challenges - Rodrigues, Joana Lúcia Lima Correia (2021)
Furanocoumarins are plant secondary metabolites used to treat several skin disorders, such as psoriasis and vitiligo, and also with other potential therapeutic activities. Furanocoumarins are extracted from plants where they accumulate in low amounts over long growth periods. In addition, their extraction and purification are difficult in an environmentally unfriendly and expensive process. Hence, new sustainable and greener production schemes able to overcome such limitations ought to be developed. While the heterologous production of simple coumarins has been demonstrated, the biosynthesis of more complex furanocoumarins remains greatly unexplored. Although several important steps of the pathway have been elucidated in the last decade, the complete pathway has not been completely unravelled. In this paper, we review the natural conversion of amino acids into furanocoumarins, as well as the heterologous expression of each enzyme of the pathway. We also explore the challenges that need to be addressed so that their heterologous production can become a viable alternative.